Equity in Tax Law: Vietnam Case Study - Le Thi Thao; Nguyen Thi Trien (Administrative and Environmental Law Review, 2022)
One of the prime principles in the optimal tax system of countries is fairness. Equity in tax law originates from two points of view: fairness on the principle of benefits (from which taxpayers take away from society) and fairness on the principle of the ability to pay taxes (income). According to economist Adam Smith, "taxes are seen as the basis of economic institutions, which can cause economic instability when there is a lack of transparency and clarity". Therefore,  fairness in tax law formulation at different stages of development of each country is considered a complete principle associated with countries' economic, social and political conditions in each period. The scope of this article, based on research regarding the history of construction and development of tax law in Vietnam through the analysis of fairness in tax obligations, tax exemption, tax administration, tax fairness and tax accountability. Proposing solutions towards ensuring fairness in completing the legal tax system in Vietnam.